Jurnal Penyuluhan: Dinamika Pengelolaan Sampah Rumah Tangga di Desa Gunung Sari Kecamatan Citeureup, Kabupaten Bogor - Francisca Gita Anjani, Pudji Muljono (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
Domestic Wasted management program is one of PT Indocement's CSR conducted in Gunung Sari Village. This research aimson the evaluation of wasted management program that has been running since 2009. The evaluation was conducted using CIPP concept from Stufflebeam by analyzing content, input, process, and final product as an outcome from this program.